New Media, Incumbency and Malaysian Politics: The Defeat of the Barisan Nasional (BN) in GE14 (2018) - Warganegara, Arizka; Febriansyah , Muhammad; Kuok Tiung, Lee (Politeia: Jurnal Ilmu Politik, 2023)
The Malaysian 14th General Election (GE14) has ended the political domination of Barisan Nasional (BN) of the last 61 years and resulted in a new discussion in Malaysian politics. The main purpose of this study is to explore the factors that caused BN to fail in the last election and to refine the incumbency theory posited by Hirano and Snyder Jr (2012) and Torcal (2014). We argue that various factors have contributed to the defeat of the BN government in the 14th GE, namely the 1MDB corruption scandal, the implementation of the progressive Good and Service Tax (GST), the rise of living costs, and the China-oriented foreign and economic policies, as well as the Mahathir factor. Our results also contribute to further developing incumbency theory. Instead of relying on traditional factor of incumbent defeat in election such as scandal and economic factors, the role of new media in spreading the news about the corruption scandal and the government’s economic underperformance have also contributed to a political shift in Malaysia.